The Coniacian–Santonian sedimentary record in southern Tanzania (Ruvuma Basin, East Africa): Planktonic foraminiferal evolutionary, geochemical and palaeoceanographic patterns. Issue 1 (9th December 2016) - Petrizzo, Maria Rose; Jiménez Berrocoso, Álvaro; Falzoni, Francesca; Huber, Brian T.; Macleod, Kenneth G.
Abstract: A 101 m thick stratigraphically complete late Coniacian–early Santonian ( ca 89 to 83 Ma) sedimentary sequence drilled in Tanzania (Tanzania Drilling Project Site 39) allows, for the first time, examination of the planktonic foraminiferal biostratigraphy and evolution, the depositional history, and geochemical patterns of the subtropical–tropical Indian Ocean region. The sedimentary succession corresponds to an outer shelf to upper slope setting and is dominated by calcareous clayey siltstones and mudstones. The occurrences of Tethyan marker species enable application of the tropical biozonation including identification of the Dicarinella concavata and Dicarinella asymetrica Zones. In addition, Tanzania Drilling Project Site 39 is proposed as reference section for the Coniacian/Santonian boundary in the Indian Ocean with the boundary placed at the lowest occurrence of Globotruncana linneiana in agreement with the Global Stratotype Section and Point (Spain). The record at Tanzania Drilling Project Site 39 provides a unique opportunity to document the planktonic foraminiferal evolution in a subtropical marginal sea environment during a key period in their evolutionary history characterized by a major radiation among the deep‐dwelling taxa. Combined documentation of lithological and geochemical changes (%CaCO3, %Corg, δ 13 Ccarb and δ 18 Ocarb ) reveals a setting influenced by continental‐derived nutrients in the Dicarinella concavata Zone (Lindi Formation) with a change to higher carbonate production and reduced surface water primary productivity in the overlying Dicarinella asymetrica Zone (Nangurukuru Formation). Planktonic foraminiferal assemblage changes mirror the depositional and geochemical trends and indicate a progressive shift from a more eutrophic to a more oligotrophic regime through time. At the local scale, this palaeoceanographic scenario is consistent with the deepening of coastal Tanzania in response to the Late Cretaceous marine transgression registered in south‐east Tanzania. Because the tectonic evolution and sea‐level rise along the East Africa continental margin is superimposed on the Coniacian–Campanian global long‐term sea‐level high, this study hypothesizes that the epicontinental invasion of blue waters may have favoured radiation among deep‐dwelling taxa.